Evaluación potencial de la construcción de un techo verde en la Universidad de América Ecocampus (2022)
Green roof structures have recently gained great importance due to the different environmental, social and economic benefits they generate. For this reason, this paper analyzes the potential for the construction of a green roof in the administrative building of the Ecocampus headquarters of the Universidad de América. A bibliographic review of the characteristics that a green roof should have for its proper functioning and the different options that exist for the choice of the substrate, vegetation, waterproofing material and the function to be implemented in the green roof is made, it is sought to find all the previous activities that must be taken into account for the construction of the same.